Transition to Advanced Heart Failure: From Identification to Improving Prognosis - Nikolaos-Iason Tepetes; Christos Kourek; Adamantia Papamichail; Andrew Xanthopoulos; Peggy Kostakou; Ioannis Paraskevaidis; Alexandros Briasoulis (Journal of Cardiovascular Development and Disease)
Advanced heart failure (AHF) represents the terminal stage of heart failure (HF), characterized by persistent symptoms and functional limitations despite optimal guideline-directed medical therapy (GDMT). This review explores the clinical definition, pathophysiology, and therapeutic approaches for AHF. Characterized by severe symptoms, New York Heart Association (NYHA) class III-IV, significant cardiac dysfunction, and frequent hospitalizations, AHF presents substantial challenges in prognosis and management. Pathophysiological mechanisms include neurohormonal activation, ventricular remodeling, and systemic inflammation, leading to reduced cardiac output and organ dysfunction. Therapeutic strategies for AHF involve a multidisciplinary approach, including pharmacological treatments, device-based interventions like ventricular assisted devices, and advanced options such as heart transplantation. Despite progress, AHF management faces limitations, including disparities in access to care and the need for personalized approaches. Novel therapies, artificial intelligence, and remote monitoring technologies offer future opportunities to improve outcomes. Palliative care, which focuses on symptom relief and quality of life, remains crucial for patients ineligible for invasive interventions. Early identification and timely intervention are pivotal for enhancing survival and functional outcomes in this vulnerable population. This review underscores the necessity of integrating innovative technologies, personalized medicine, and robust palliative strategies into AHF management to address its high morbidity and mortality.